Composition and Dynamics of H1N1 and H7N9 Influenza A Virus Quasispecies in a Co-infected Patient Analyzed by Single Molecule Sequencing Technology - Lin, Peng; Jin, Tao; Yu, Xinfen; Liang, Lifeng; Liu, Guang; Jovic, Dragomirka; Sun, Zhou; Yu, Zhe; Pan, Jingcao; Fan, Guangyi (Frontiers in Genetics, 2021)
The co-infection with two subtypes of influenza virus pathogenesis is a complex disease. The utterly understanding of viral genome variation is a basis of precision medicine for complex infectious diseases. Revealing the composition and dynamics of influenza A virus (IAV) quasispecies is a core to explore how a viral population rapidly adapt to host environments and selective pressure shifts. Therefore, in this study we acquired full-length genomes of a viral population to characterize the quasispecies composition. Using long sequencing reads produced by single-molecule real-time sequencing (SMRT) technology, we successfully quantified the abundance of all genotypes of full-length influenza A virus genomes in eight serial samples from an 81-year-old male co-infected with Influenza H1N1 and H7N9 subtypes and revealed the composition and dynamics of viral quasispecies. A total of 26 high diversity nucleotide loci was observed, in which the A-G base transition was the most abundant substitution type (67% and 64%, in H1N1 and H7N9, respectively). In addition, we found several significant amino acid variations, which are related to viral drug-resistance or mammalian adaptation such as NA:H275Y and HA: R222K in H1N1 as well as PB2:E627K and NA: K432E in H7N9. We also enlightened that the combining bases on high-diversity nucleotide loci in one genomic sequence might be considered as the haplotype characterization to simplify quasispecies composition. We confirmed the discrepant space-time abundance distribution of H1N1 and H7N9 quasispecies in serial samples from the different respiratory tract positions of this patient. Our approach promotes the popularization of viral quasispecies analysis, which will boost the understanding of viral infections, pathogenesis, evolution, and precision medicine. 9